Spectrophotometric Determination of Carbosulfan in Formulations and Water Samples - Rama Mohan, K.; Venkateswarlu, B.; Seshaiah, K. (Asian Journal of Chemistry, 2010)
A sensitive spectrophotometric method for the determination ofcarbosulfan pesticide in formulations and water samples isdescribed. The method is based on the alkaline hydrolysis of thepesticide and the resultant phenol is reacted with 4-aminoantipyrinein the presence of an oxidizing agent. The resultant colored dye isextracted into chloroform and the absorbance is measured at480 nm.